Biomechanical analysis of elite javelin thrower of Pakistan - Nazeer, M. T.; Tahir, M. A.; Walee, R. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study investigated the biomechanical factors influencing javelin throwing performance among elite Pakistani athletes. Eight national-level male throwers were analyzed using 3D motion capture during the 2024 National Athletics Championships. Key variables included release velocity components, approach run velocity, pull distance, and phase durations. Results showed that vertical release velocity and approach run velocity at right foot touchdown (R-on) were significantly correlated with throwing distance (r = 0.672, p < .05 and r = 0.596, p < .05, respectively). No significant correlations were observed for pull distance, step length, or phase durations. Findings suggest that elite performance relies on maximizing vertical release while maintaining sufficient horizontal speed, emphasizing the importance of individualized technical training in Pakistan`s javelin development programs.